2022
DOI: 10.1007/s00423-022-02541-5
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass and post-operative complications after surgery for liver malignancies: a meta-analysis

Abstract: Purpose To assess the influence of low skeletal muscle mass (LSMM) on post-operative complications in patients with hepatic malignancies grade (Clavien Dindo ≥ 3) undergoing resection. Methods MEDLINE, Cochrane, and SCOPUS databases were screened for associations between sarcopenia and major post-operative complications (≥ grade 3 according to Clavien-Dindo classification) after resection of different malignant liver tumors. RevMan 5.3 software was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The results revealed a robust association between sarcopenia and/or SO and patient survival. A strong relationship between sarcopenia and adverse clinical outcomes in cancer patients has been reported in prior studies, including depression ( 83 ), risk of fall ( 84 ), higher risk of complications ( 85 ), and cancer recurrence and mortality ( 9 , 13 , 15 , 86 ). In 2022, a meta-analysis comprising 280 publications involving 81,814 patients with solid tumors demonstrated that sarcopenia is a prevalent condition in oncological patients with a prevalence of 35.3%; moreover, it is particularly higher in patients with specific cancer types such as esophageal cancer, urothelial cancer, cholangiocarcinoma, prostate cancer, and thyroid cancer ( 87 ).…”
Section: Discussionmentioning
confidence: 84%
“…The results revealed a robust association between sarcopenia and/or SO and patient survival. A strong relationship between sarcopenia and adverse clinical outcomes in cancer patients has been reported in prior studies, including depression ( 83 ), risk of fall ( 84 ), higher risk of complications ( 85 ), and cancer recurrence and mortality ( 9 , 13 , 15 , 86 ). In 2022, a meta-analysis comprising 280 publications involving 81,814 patients with solid tumors demonstrated that sarcopenia is a prevalent condition in oncological patients with a prevalence of 35.3%; moreover, it is particularly higher in patients with specific cancer types such as esophageal cancer, urothelial cancer, cholangiocarcinoma, prostate cancer, and thyroid cancer ( 87 ).…”
Section: Discussionmentioning
confidence: 84%
“… 38 and a meta-analysis by Thorman et al . 39 . The latter study described the effect of sarcopenia on severe complications (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first meta-analysis that deals with the influence of sarcopenia on the outcome of patients who undergo liver resection for colorectal liver metastases (CRLM) alone. CRLM patients have been incorporated into previous meta-analyses ( 36 , 37 ). However, due to the unique nature of CRLM and its rising incidence, preoperative assessment is more and more valued in this patient cohort ( 38 ).…”
Section: Discussionmentioning
confidence: 99%